2018
DOI: 10.3171/2017.5.jns17642
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage associated with ventriculoperitoneal shunt placement in aneurysmal subarachnoid hemorrhage patients on a regimen of dual antiplatelet therapy: a retrospective analysis

Abstract: This clinical series confirms that, in patients with ruptured aneurysms who are candidates for stent-assisted coiling or flow diversion, the risk of clinically significant VP shunt-associated hemorrhage with DAPT is low. In an era of evolving endovascular therapeutics, stenting or flow diversion is a viable option in select aSAH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 18 publications
2
19
0
1
Order By: Relevance
“…With regard to DAPT, two recent studies by Hudson et al demonstrate a higher risk for radiographic hemorrhage associated with external ventricular drain or VP shunt placement in aSAH patients requiring DAPT due to stent-assisted coiling or flow diversion. However, the risk of clinically significant bleeding complications was considered low [21,22]. A recent meta-analysis [5] reported that ventriculostomy-related bleeding rates were significantly higher among patients receiving APT and that the rate of major hemorrhage was higher after DAPT compared with single APT.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to DAPT, two recent studies by Hudson et al demonstrate a higher risk for radiographic hemorrhage associated with external ventricular drain or VP shunt placement in aSAH patients requiring DAPT due to stent-assisted coiling or flow diversion. However, the risk of clinically significant bleeding complications was considered low [21,22]. A recent meta-analysis [5] reported that ventriculostomy-related bleeding rates were significantly higher among patients receiving APT and that the rate of major hemorrhage was higher after DAPT compared with single APT.…”
Section: Discussionmentioning
confidence: 99%
“…A Korean study found that prolonged partial thromboplastin time was major risk factor of DICH 11 . Some studies showed that dual antiplatelet therapy and postoperative anticoagulation therapy would increase the risk of DICH 10 , 23 . As for our study, we excluded the patients with anticoagulant or antiplatelet therapy in order to control the confounding factors, and we found that preoperative PT, APTT, INR and PLT were not risk factors for DICH.…”
Section: Discussionmentioning
confidence: 99%
“…A Korean study found that prolonged partial thromboplastin time was major risk factor of DICH 18 . Some studies showed that dual antiplatelet therapy and postoperative anticoagulation therapy would increase the risk of DICH 17,23 . As for our study, we excluded the patients with anticoagulant or antiplatelet therapy in order to control the confounding factors, and we found that preoperative PT, APTT, INR and PLT were not risk factors for DICH.…”
Section: Discussionmentioning
confidence: 99%